Conceptual Model of Expectant Psychological Characteristics of Effective First Grade Teachers Based on Expert’s Point of View - Mashayekhipour, Mostafa; Nasri, Sadeqh; Dortaj, Fariborz (Iranian Journal of Educational Sociology, 2022)
Purpose: This study aims to infer the perception of experts about the psychological characteristics of effective teachers to clarify the angles and dimensions of the psychological characteristics of teachers. Methodology: The method of the present research is a qualitative phenomenon of phenomenological type, which has been purposefully selected from among experts in the field of psychology, especially educational psychology, and those who are directly related to the discussion of education, up to 12 people. And interviewed. The interview was first recorded with the permission of the interviewer and then turned into a text and sentences and phrases were analyzed using the Colaizzi method. Findings: According to the findings of interviews with experts in the field of education, the psychological characteristics of an effective teacher included eight themes, which were: 1. Behavior in the classroom including helpful, resilient, committed and motivated, 2. How to interact, including student’s comfort, listening, emotional relationship and having a simple expression, 3. Psychological ability including logical thinking, critical thinking, high emotional intelligence, self-confidence, social personality type and optimism, 4. Expressive skills including appropriate body language characteristics, large vocabulary, persuasive skills, 5. Mental health, 6. Creativity, 7. Ethics and 8. Discipline, including the characteristics of having mental order, regular knowledge, keeping promises and coming to class on time. Conclusion: The results showed that an effective teacher has psychological abilities in the field of thinking, including logical and critical thinking, to improve the teaching process in the classroom by creating challenges and paying attention to details. On the other hand, an effective teacher needs intelligence. It is a high emotion to build a constructive relationship, which in this connection also requires confidence so that an effective teacher can attract students in the classroom with a decisive and confident presentation.